Effectiveness and Safety of Double-balloon Catheter versus Intra-amniotic Injection of Ethacridine Lactate for Termination of Second Trimester Pregnancy in Patients with Liver Dysfunction - 李娜 吴鹏 赵捷 冯玲 乔福元 曾万江 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
Severe liver dysfunction in pregnancy（SLDP） is rare but serious complications with high mortality rate. This study compared the effectiveness and safety of double-balloon catheter versus intra-amniotic injection of ethacridine lactate for the termination of second trimester pregnancy in patients with SLD. A total of 55 patients with indications of labor induction were enrolled and analyzed by retrospective control analysis method. Twenty-three cases adopted Cook double balloon dilation as Cook group, and 32 cases received intra-amniotic injection of ethacridine lactate as EL group. The primary outcome was evaluated by successful abortion rate and the difference in the induction-to-abortion interval. Secondary outcomes included liver function recovery and the frequency of adverse events. Both Cook and EL regimens were effective, with successful abortion rate of 87.0% and 93.8%, respectively（P=0.639）. The induction-to-delivery interval was similar between Cook group and EL group（38.1±21.5 vs. 41.3±17.4, P=0.543）. The liver disease status was more severe in Cook group than in EL group, but it did not show any significant difference after pregnancy termination between the two groups and the improvement rate also did not show any significant difference. Both treatments were safe and there was no significant difference in bleeding and cervical laceration adverse events between the two groups. Our study firstly compared double-balloon catheter and ethacridine lactate for the induction of labor in women with SLD during second trimester pregnancy.